CARBON CYCLING AT ANCIENT METHANE-SEEPS - Peckmann J.; Thiel V. (My University, 2004)
The oldest known seep deposits with macroinvertebrate taxa are Devonian in age. Although more and more examples continue to be discovered, the Palaeozoic and Mesozoic record of methane–seeps is still fragmentary. The relationship of ancient carbonate deposits to methane seepage is established by (i) the geological setting and structural features, (ii) the occurrence of low diversity but high abundance faunal assemblages, (iii) carbonate fabrics, (iv) low δ13C values of early diagenetic carbonate phases, and (v) characteristic 13C-depleted biomarkers. In this review, special emphasis is placed on biogeochemical processes at ancient methane–seeps. Specific carbonate fabrics and phases include, in order of decreasing significance for seep-dominated environments, (i) inverted stromatactoid cavities, (ii) upside-down stromatolites, (iii) globular fabrics, (iv) botryoidal aragonite, (v) micritic nodules, (vi) fractures, (vii) clotted micrites, and (viii) constructive seams representing fossilised biofilms. The carbon of the early diagenetic carbonate phases was derived predominantly from the oxidation of methane which resulted in low δ13C values. Pyrites enclosed in the seep limestones generally show low δ34S values and a significant variability of their isotopic composition on a small scale, both indicating bacterial sulphate reduction as the sulphide-supplying process. 13C-depleted lipid biomarkers characterise the microbial populations involved in the cycling of carbon at ancient methane–seeps. Typical compounds include isoprene-based lipids from archaea, and linear and monomethyl-branched carbon skeletons assigned to sulphate-reducing bacteria (SRB), consistent with the syntrophic relationship of these microbes in the anaerobic oxidation of methane (AOM).